Sex-Specific Patterns of Aging in Sexual Ornaments and Gametes - Cornwallis, C; Dean, R; Pizzari, T (University of Chicago Press, 2014)
Sex differences in age-dependent mortality and reproductive success are predicted to drive the evolution of sexually dimorphic patterns of reproductive investment over life. However, this prediction has not been fully explored because it is difficult to measure primary and secondary sexual traits over the life spans of males and females. Here we studied a population of fowl, Gallus gallus, to gain longitudinal data on a sexual ornament (the comb), quantity of gametes produced, and gamete quality (sperm velocity and egg mass) of males and females. Our results reveal pronounced differences between the sexes in age-specific patterns of reproductive investment. In males, comb size decreased linearly with age, high sperm quality early in life was associated with reduced sperm quality late in life, and high sperm production was related to early death. In contrast, female comb size and egg mass were maximized at intermediate ages, and fecundity was independent of life span. Finally, the way traits were related in males did not change over life, whereas in females the association between fecundity and comb size changed from positive to negative over the lifetime of a female, indicating that aging may lead to trade-offs in investment between traits in females. These results show that males and females differ in reproductive investment with age, in terms of both the expression of individual traits and their phenotypic covariance.